Comparison of Fusobacterium nucleatum and porphyromonas gingivalis lipopolysaccharides clinically isolated from root canal infection in the induction of pro-inflammatory cytokines secretion - Martinho, Frederico C. [UNESP]; Leite, Fábio R. M.; Nóbrega, Letícia M. M. [UNESP]; Endo, Marcos S. [UNESP]; Nascimento, Gustavo G.; Darveau, Richard P.; Gomes, Brenda P. F. A. [UNESP] (FapUNIFESP (SciELO), 2016)
The aim of this study was to compare the biological activity of lipopolysaccharides (LPS) purified from Fusobacterium nucleatum and Porphyromonas gingivalis strains, both isolated from primary endodontic infection (PEI) in the levels of IL-1β and TNF-α released by macrophage cells. Moreover, LPS was purified from F. nucleatum and P. gingivalis American Type Collection (ATCC) and its biological activity was compared to respectively clinical isolates strains. F. nucleatum and P. gingivalis strains clinically isolated from PEI had their identification confirmed by sequencing the 16S rRNA gene. LPS from F. nucleatum and P. gingivalis and their respective ATCC strains were extracted by using Tri-reagent method. Macrophages (Raw 264.7) were stimulated with LPS at 100 ng/mL for 4, 8 and 12 h. Secretion of IL-1□ and TNF-α was also determined. Paired t-test, repeated measures ANOVA and one-way ANOVA were employed. All LPS induced significant production of IL-1β and TNF-α, with the former being secreted at higher levels than the latter in all time-points. F. nucleatum induced a higher expression of both cytokines compared to P. gingivalis (p<0.05). No differences were observed between clinical and ATCC strains, as both presented the same potential to induce pro-inflammatory response. It was concluded that F. nucleatum and P. gingivalis LPS presented different patterns of activation against macrophages as seen by the IL-1β and TNF-α production, which may contribute to the immunopathogenesis of apical periodontitis. Moreover, clinical and ATCC strains grown under the same in vitro environment conditions presented similar biological activity.
Keywords: Bacteria; Cytokines; Endodontics; Endotoxin; Fusobacterium nucleatum; LPS; Macrophages; Porphyromonas gingivalis